APPLICATION OF POTASSIUM NUTRITION SUPPLY TO SHALLOT PLANTS UNDER SMART K – SPRINKLE FERTIGATION IN DRY LAND - Nur Iman Muztahidin; Alfu Laila; Mona Sari; Andi Apriany Fatmawati; Nuniek Hermita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
The purpose of this study was to investigate smart k – sprinkle fertigation in dry land with potassium nutrition supply on growth and yield of shallot plants. The study was conducted in the Research Field Department of Agroecotechnology, Faculty of Agriculture, University of Sultan Ageng Tirtayasa, Indonesia from August to November 2020. The experiment was designed in a Randomized Complete Block Design (RCBD) with four replications. Experiment was conductedin six different treatments as K50: Potassium nutrition of 50 kg.ha-1 under smart K – sprinkle fertigation system; K75: Potassium nutrition of 50 kg.ha-1 under smart K – sprinkle fertigation system; K100: Potassium nutrition of 50 kg.ha-1 under smart K – sprinkle fertigation system; K125: Potassium nutrition of 50 kg.ha-1 under smart K – sprinkle fertigation system; K150: Potassium nutrition of 50 kg.ha-1 under smart K – sprinkle fertigation system; Control: conventional fertilizer of 100 kg.ha-1 as basal dose recommendation. The results showed thatsmart K – sprinkle fertigation system revealed to increase shallot plant on growth and yield. Besides, the use of Potassium nutrition of 50 kg.ha-1 (K50 treatment) showed the highest value on number of leaves plant weight, and bulbs weight per plant, as well as on the potential yields. So that, further study is recommend to observe the application of smart K – sprinkle fertigationsystem in combination with other nutrition.Keywords: potassium, fertilizer, micro sprinkle, onion